Pelatihan merias wajah untuk ibu-ibu dharma wanita dan remaja putri putus sekolah di Desa Rompegading - Kurniati Kurniati (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The partner of this Community Service Program (PPM) was the dharma wanita team and adolescent girls who drop out of school in Rompegading Village. The problems were: (1) the partner group members are not able to use makeup equipment properly and correctly, (2) the trainees have minimal makeup skills so they feel less confident to perform at party events, and (3) the partners need special makeup services (salons or makeup artists) with varied costs and even expensive fees for professional makeup. After the makeup training, it is expected that partners have special skills to apply makeup with satisfying results. The results achieved were (1) the partners knew the technique of using makeup equipment appropriately, (2) Each member in the partner group claimed to feel confident to perform at the party, and (3) the training participants said they would not incur additional costs for special makeup services (salons or makeup artists) because they already have their own makeup skills.